Volatile Compounds from Grape Skin, Juice and Wine from Five Interspecific HybridGrape Cultivars Grown in Québec (Canada) for Wine Production - Slegers, Amélie (Molecules, 2015)
Developed from crosses between Vitis vinifera and North American Vitis species, interspecific hybrid grape varieties are becoming economically significant in northern areas, where they are now extensively grown for wine production. However, the varietal differences between interspecific hybrids are not well defined, nor are the relationships between hybrid grape and wine composition, which causes significant drawbacks in the development of viticulture and winemaking of northern wines. In an effort to increase our understanding of interspecific hybrids, we have characterized the free volatile compounds profiles of berries (juice and skin) and wines of five red hybrid varieties (Frontenac, Marquette, Maréchal Foch, Sabrevois and St. Croix) grown in Québec (Canada), using GC-MS(TOF)-SPME. In grapes and wines, significantly higher levels of C(6) and other fatty acid degradation products (FADP) were found in Frontenac, Maréchal Foch and Marquette. Terpenes were primarily located in the skin, with Marquette showing the highest level for these compounds. Both the level of terpenes and the level of FADP in grape were strongly correlated with their respective levels in wine, as demonstrated by the redundancy analyses. Nonanal, (E,Z)-2,6-nonadienal, β-damascenone, ethyl octanoate and isoamyl acetate showed the highest OAVs in the wines of the studied varieties.